Gamification in Social Media Marketing Strategy to Enhance Customer Loyalty of MSME Products - Hairul Anwar; Said Muhammad; Huda Sya'rawi (Citakonsultindo, 2025)
This study aims to analyze the role of gamification strategies in social media marketing to increase customer loyalty among Micro, Small, and Medium Enterprises (MSMEs). In the era of growing digital competition, MSMEs need innovative approaches to attract and retain customers. Gamification, as an engagement-based marketing technique, leverages game elements such as rewards, leaderboards, and challenges to create interactive consumer experiences. This research employed a mixed-method design combining quantitative analysis (correlation and t-test) and qualitative insights to evaluate the impact of gamification on customer engagement and loyalty. The findings indicate a significant positive relationship between gamification strategies and customer loyalty, with gamified content on social media platforms proving effective in encouraging repeat purchases and strengthening brand attachment. The study contributes to marketing literature by providing empirical evidence of gamification effectiveness as a cost-efficient and scalable marketing tool for MSMEs. Practical recommendations are also provided for MSME practitioners in designing customer-centered campaigns to maximize engagement and loyalty in the evolving digital ecosystem.